PENGARUH MASA SIMPAN MADU KELULUT (Trigona SP) TERHADAP KADAR GULA PEREDUKSI DAN KEASAMAN - Iis Karnia; Siti Hamidah; Gusti Akhmad Rahmad Thamrin (Jurnal Sylva Scienteae, 2020)
This study is to determine the quality of honey at various storage times  in 2016 (A1), 2017 (A2), 2018 (A3). Parameters tested were reducing sugar content and acidity.The results of testing the quality of honey are determined based on the Indonesian National Standard (SNI) 01-3545: 2013. The results of testing the quality of kelulut honey (Trigona sp) until the age of 2 years are better when viewed from reducing sugar content. The reducing sugar level is set at a minimum of 65% b / b. Honey A1 (2016) with the highest sugar content of 67.2%. A2 honey sugar content (2017) is 66.5%. While A3 honey (2018) only reached 60.7%. Kelulut honey that is still fresh or stored until the age of 2 years cannot reach the SNI for its acidity. The acidity of honey in A1 (2016) reached 295.82 ml NaOH / Kg, A2 (2017) 369.06 ml NaOH / Kg, and the others A3 (2018) 474.34 ml NaOH / Kg. it's too acidic (> 50 ml NaOH / Kg). The high levels of honey acidity reduce the quality of kelulut honey, but the acidity of honey decreases, seen from the longer storage time.Keywords: Trigona Sp, Kelulut Honey, Quality of honey , Reducing Sugar, acidity of honey